Implementasi Pendidikan Akhlak Melalui Metode Storytelling Interaktif Pada Anak Usia Dini - Afifah Nurul Hidhayah; Nur Tanfidiyah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Write the abstract in English and the maximum English Based on this, the aim of this research is to find out how moral education is implemented through the interactive storytelling method for early childhood at TKIT Mutiara Insan Sukoharjo in the 2023 academic year. The type of research used is descriptive qualitative research. Data collection techniques used participatory observation methods, semi-structured interviews and documentation. The data validity technique uses triangulation techniques and sources, while the data analysis technique uses data collection, data condensation, data presentation and conclusions. The results of the research are, the use of interactive storytelling methods in strengthening moral education at TKIT Mutiara Insan is carried out through the stages of learning planning, learning implementation and evaluation. At the planning stage the teacher prepares the RPPH, the implementation stage the teacher carries out 3 steps: opening the teacher greets and conveys the material, the main activity is the teacher telling stories with a theme that is in accordance with the curriculum, asking questions, conveying messages, closing the teacher recalling what has been done. studied. The evaluation stage is carried out every day at the end of the lesson using checklist and anecdotal assessments. Abstrak